2006
DOI: 10.1117/12.659048
|View full text |Cite
|
Sign up to set email alerts
|

Fiber grating sensors for structural health monitoring of aerospace structures

Abstract: Fiber optic grating sensors can be used to measure multi-dimensional strain, pressure, temperature, corrosion and moisture. The application of this technology to structural health monitoring of aerospace platforms includes adhesive bond line measurements, crack detection, damage assessment of composite and moisture/corrosion sensing. One very important application is the emerging field of "strain imaging" that can be used in certain situations to detect, localize and characterize damage in composites. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…[1][2][3][4] Some of the key parameters to be monitored for SHM are temperature, humidity, acidity, salinity, UV radiation, carbonization, deformation, strain, fatigue damage, and corrosion. Therefore, SHM systems can consist of a wide number of sensors and transmission systems for an adequate data management and health diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Some of the key parameters to be monitored for SHM are temperature, humidity, acidity, salinity, UV radiation, carbonization, deformation, strain, fatigue damage, and corrosion. Therefore, SHM systems can consist of a wide number of sensors and transmission systems for an adequate data management and health diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…They are lightweight, small in size and electromagnetically immune. Several studies have shown the potential of FOS in space [1][2][3][4][5]. Their small size and multiplexing capability makes them very suitable for structural integration.…”
Section: Introductionmentioning
confidence: 99%
“…With the recent application of inverse scattering methods, such as the Born approximation method [1], a layer-peeling algorithm (LPA) [2] or a genetic algorithm [3], the refractive * This paper is the work of an agency of the US government and is not subject to copyright. index changes due to environmental strain and temperature influences are detectable on scales smaller than the FBG length.…”
Section: Introductionmentioning
confidence: 99%
“…index changes due to environmental strain and temperature influences are detectable on scales smaller than the FBG length. This has been applied to measuring nonuniform strain fields as well as highly localized strains by direct measurement of the stress-optic or thermal-optic induced changes in the refractive index [3][4][5][6][7][8][9][10][11][12]. These methods have been shown to provide spatial resolutions near 10 µm, limited by the source bandwidth.…”
Section: Introductionmentioning
confidence: 99%